Migration and poverty : toward better opportunities for the poor - Murrugarra, Edmundo; Larrison, Jennica; Sasin, Marcin J.; World Bank. (Washington, D.C. : World Bank, 2011)
Research presented in this book shows how migration expands the choices available to poor people and how it can contribute significantly to alleviating poverty.
Includes bibliographical references and index.
rua 26/08/13, ijb 21/02/2019
Loans
Keywords: Poverty; Emigration and immigration - government policy; Emigration and immigration - economic aspects; Developing countries